Evaluating the Protective Role of Intranasally Administered Avian-Derived IgY Against SARS-CoV-2 in Syrian Hamster Models - Mónika Madai; Dániel Hanna; Roland Hetényi; Fanni Földes; Zsófia Lanszki; Brigitta Zana; Balázs Somogyi; Henrietta Papp; Anett Kuczmog; Orsolya Faragó-Sipos; Csaba Nemes; Vilmos Palya; et al. (Vaccines)
Background/Objectives: The ongoing COVID-19 pandemic has underscored the need for alternative prophylactic measures, particularly for populations for whom vaccines may not be effective or accessible. This study aims to evaluate the efficacy of intranasally administered IgY antibodies derived from hen egg yolks as a protective agent against SARS-CoV-2 infection in Syrian golden hamsters, a well-established animal model for COVID-19. Methods: Hens were immunized with the spike protein of SARS-CoV-2 to generate IgY antibodies. These antibodies were extracted from the egg yolks, purified, and their neutralizing activity was tested in vitro. Syrian golden hamsters were then treated with the IgY antibodies before being challenged with SARS-CoV-2. Viral loads were quantified using droplet digital PCR (ddPCR), and lung pathology was assessed through histopathological analysis. Results: The in vitro assays showed that IgY effectively neutralized SARS-CoV-2. In the in vivo hamster model, IgY treatment led to a significant reduction in viral loads and a marked decrease in lung consolidation and inflammation compared to the positive control group. Histopathological findings further supported the protective role of IgY in reducing lung damage caused by SARS-CoV-2. Conclusions: The results demonstrate that IgY antibodies exhibit strong antiviral activity and can significantly reduce SARS-CoV-2 viral loads and associated lung pathology in hamsters. These findings suggest that IgY could be a viable prophylactic option for preventing SARS-CoV-2 infection, particularly for individuals who cannot receive or respond to vaccines. Further studies are warranted to optimize dosage and explore the long-term efficacy of IgY antibodies.